2019
DOI: 10.7567/1347-4065/ab21a5
|View full text |Cite
|
Sign up to set email alerts
|

Device modeling of amorphous oxide semiconductor TFTs

Abstract: Device models of amorphous oxide semiconductor thin-film transistors (AOS TFTs) associate AOS carrier transport and electronic states with AOS TFT electrical characteristics. Thus, such models are very useful for estimation and analysis on operations and reliability of AOS TFTs and developments of electronic devices with AOS TFTs. We discuss the models including mobility models and density of subgap state (DOS) models, which reflect the carrier-electron transport and the electronic states of AOSs. A device sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…Unlike silicon FETs, the mobility of a -IZTO TFTs increases with T , and this relationship describes the percolation conduction mechanism (Figure ). The percolation conduction mechanism, as an electron mobility model, comes from spatial E C edge fluctuation due to nanoscale composition variations in amorphous multi-component oxide TFTs. The relationships among μ eff , effective field ( E eff ), and electron density ( n e ) can be obtained from I acc = I normalD ( V GS ) I normalD ( V FB ) = W L μ eff Q normals V DS E eff = true∫ 0 x n ( x ) E ( x ) normald x true∫ 0 x n ( x ) normald x = Q normals 2 ε normals where Q s is the sheet charge density, which is equal to (− q ) × T ch × n e , and ε s is the permittivity of the semiconductor. Only accumulation-charge current ( I acc ) by electrons was calculated because the a -IZTO TFT operates in accumulation mode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike silicon FETs, the mobility of a -IZTO TFTs increases with T , and this relationship describes the percolation conduction mechanism (Figure ). The percolation conduction mechanism, as an electron mobility model, comes from spatial E C edge fluctuation due to nanoscale composition variations in amorphous multi-component oxide TFTs. The relationships among μ eff , effective field ( E eff ), and electron density ( n e ) can be obtained from I acc = I normalD ( V GS ) I normalD ( V FB ) = W L μ eff Q normals V DS E eff = true∫ 0 x n ( x ) E ( x ) normald x true∫ 0 x n ( x ) normald x = Q normals 2 ε normals where Q s is the sheet charge density, which is equal to (− q ) × T ch × n e , and ε s is the permittivity of the semiconductor. Only accumulation-charge current ( I acc ) by electrons was calculated because the a -IZTO TFT operates in accumulation mode.…”
Section: Resultsmentioning
confidence: 99%
“…Oxide semiconductor platforms including a -IGZOs have several merits, including high μ FE , uniformity, bias-stress reliability, and an extremely low I OFF of 10 –20 A. Oxide semiconductor TFTs are used as standard switching devices in backplane electronics for large OLED televisions and are expected to be used in high-end, small- and medium-sized OLED displays. Most oxide semiconductor substances have n-type characteristics and a unique electron-conduction mechanism [so-called percolation conduction], in which electron mobility increases with electron concentration and temperature. The local temperature in an oxide semiconductor channel region is determined by a self-heating phenomenon based on the Joule effect, which can cause an increase in I ON and a negative shift in V TH . An unintentional increase in the I ON of the pixel driver will adversely affect the brightness of an OLED pixel. Grayscales in a self-emitting OLED pixel vary from <1 nA (black) to >1 μA (full white).…”
Section: Introductionmentioning
confidence: 99%
“…Hsieh et al reported that the conduction band tail state extending from the conduction band minimum (CBM) originates from the variation of the M-O bonding angle in the a-IGZO semiconductor . By TCAD simulation, other XPS components (V O ) and −OH are understood as contributing as part of the Gaussian distributed donor-like and acceptor-like DOS, respectively . Kim et al reported the Zn cation disordering and V O defects from XPS analysis as acceptor-like tail states and shallow donor-like states, respectively .…”
Section: Results and Discussionmentioning
confidence: 99%
“…17 By TCAD simulation, other XPS components (V O ) and −OH are understood as contributing as part of the Gaussian distributed donor-like and acceptor-like DOS, respectively. 23 Kim et al reported the Zn cation disordering and V O defects from XPS analysis as acceptorlike tail states and shallow donor-like states, respectively. 24 Seul et al also reported high field-effect mobility ZnO/IGO heterojunction TFTs and considered V O defects as donorlike deep states.…”
Section: ■ Results and Discussionmentioning
confidence: 99%